2002
DOI: 10.1021/es010293b
|View full text |Cite
|
Sign up to set email alerts
|

Solubility-Normalized Combined Adsorption-Partitioning Sorption Isotherms for Organic Pollutants

Abstract: Equilibrium sorption isotherms were measured for five different low-polarity organic compounds (benzene, trichloroethene, 1,2- and 1,4-dichlorobenzene, and phenanthrene) over a wide concentration range. The investigated sorbents can be grouped into the following three classes: (1) humic soil organic matter, which shows linear sorption isotherms (solely partitioning, as observed in the peat sample); (2) carbon materials, which were thermally altered (due to their natural history or industrial production) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
171
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 56 publications
20
171
1
Order By: Relevance
“…Some studies have indicated that porosity and surface properties of NOM play a significant role in controlling the sorption (Kleineidam et al, 2002;Pignatello, 2012;Ran et al, 2002Ran et al, , 2004Ran et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that porosity and surface properties of NOM play a significant role in controlling the sorption (Kleineidam et al, 2002;Pignatello, 2012;Ran et al, 2002Ran et al, , 2004Ran et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…partitioning, non-covalent and covalent binding) is usually evaluated by sorption isotherms conforming to various theoretical models: Freundlich, Langmuir, Polanyi-Dubinin-Manes, etc. (Aboul-Kasim & Simoneit, 2001;Kleineidam et al, 2002). The most frequently used method to obtain the experimental data for isotherm construction remains the batch equilibrium method (Celano et al, 2008;Kleineidam et al, 2002;Konda et al, 2002;Kovaios et al, 2006;Lima et al, 2009;Ling et al, 2006;Stipičević et al, 2009).…”
Section: Elucidation Of Triazine Fate In the Soil As Influenced By Anmentioning
confidence: 99%
“…(Aboul-Kasim & Simoneit, 2001;Kleineidam et al, 2002). The most frequently used method to obtain the experimental data for isotherm construction remains the batch equilibrium method (Celano et al, 2008;Kleineidam et al, 2002;Konda et al, 2002;Kovaios et al, 2006;Lima et al, 2009;Ling et al, 2006;Stipičević et al, 2009). Other approaches are by chromatographic estimation (Bermudez-Saldana et al, 2006) or indirectly by structural descriptors (Schüürmann et al, 2006).…”
Section: Elucidation Of Triazine Fate In the Soil As Influenced By Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial degradation of aromatic hydrocarbons is hampered for three reasons: Firstly, because of the high activation energy needed to chemically attack aromatic rings (Boll et al, 2002), secondly by the substances' toxicities towards bacteria (Jonker et al, 2006;Loibner et al, 2004), and thirdly because aromatic hydrocarbons have a tendency to sorb on hydrophobic surfaces. This tendency is increasing with the number of their aromatic rings (Kleineidam et al, 2002;Kubicki, 2006). Sorption and poor solubility in water makes the major fraction of PAHs inaccessible for bacterial degradation (Bosma et al, 1997;Volkering et al, 1992).…”
Section: Introductionmentioning
confidence: 99%